HEALTH PROPERTIES AND THERAPEUTIC POTENTIAL OF YERBA MATE (ILEX PARAGUARIENSIS) IN HEALTHCARE: A COMPREHENSIVE REVIEW - Aleksandra Trojańska; Karol Śliwa; Anita Pieńkowska; Paulina Malon; Nel Geworkian; Natalia Hariasz; Martyna Pietz; Anita Szymańska (International Journal of Innovative Technologies in Social Science, 2026)
Yerba mate (Ilex paraguariensis) has emerged as a promising nutraceutical with pleiotropic metabolic and immunomodulatory effects relevant to cardiovascular risk modification, obesity care, glycemic control, oxidative stress, gut immune homeostasis, and inflammatory bowel disease. Randomized clinical data demonstrate reductions in body fat mass, percent body fat, and waist–hip ratio without safety concerns after 12 weeks of standardized supplementation, aligning with mechanistic rodent work showing tissuespecific bioenergetic reprogramming, antiinflammatory signaling, improved mitochondrial coupling in muscle, adipose thermogenic uncoupling, and enhanced hepatic redox tone. Metaanalytic evidence on lipids remains inconclusive overall, though individual trials report favorable LDLC signals in dyslipidemia, including addon effects to statins. Preclinical and translational studies indicate attenuation of hypothalamic and adipose inflammation, improved insulin signaling via PI3K–AKT pathways, modulation of macrophage polarization toward M2 phenotypes, and microbiota shifts that may augment metabolic and intestinal antiinflammatory activity. Safety signals are generally favorable when consumed in moderate amounts, with attention to preparation practices to minimize polycyclic aromatic hydrocarbons and to manganese intake with very high volume use. This narrative synthesizes clinically salient evidence and proposes patient-oriented use of yerba mate in cardiometabolic risk reduction, weight management, and adjunctive care in colitis, while outlining dosing, formulation, and monitoring considerations and research priorities.